2021
DOI: 10.1063/5.0068594
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on physical modeling of flow mechanism in volumetric fracturing of tight oil reservoir

Abstract: This paper investigates the characteristics of oil–water two-phase flow after volumetric fracturing of horizontal wells in tight reservoirs. Based on a large-scale high-pressure, high-temperature experimental system for modeling horizontal well injection and production, the characteristics of the pressure distribution, cumulative liquid production, recovery factor, and liquid production rate of a matrix model and fractured model during the waterflooding process are compared and analyzed. The results show that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The calculated results show that the density of methane inclusions in the Longmaxi shale fracture calcite veins in well H201 varied from 0.257 to 0.275 g/cm 3 and that of the Wufeng-Longmaxi shales in well H202 varied from 0.274 to 0.285 g/cm 3 .…”
Section: Microthermometry Of Methane Inclusionsmentioning
confidence: 95%
See 3 more Smart Citations
“…The calculated results show that the density of methane inclusions in the Longmaxi shale fracture calcite veins in well H201 varied from 0.257 to 0.275 g/cm 3 and that of the Wufeng-Longmaxi shales in well H202 varied from 0.274 to 0.285 g/cm 3 .…”
Section: Microthermometry Of Methane Inclusionsmentioning
confidence: 95%
“…where ρ is the density of methane inclusions (g/cm 3 ) and D = v 1 − v 0 , in which v 1 is the measured methane Raman scattering peak of methane inclusions and v 0 is the methane Raman scattering peak of methane inclusions when the pressure is close to 0.…”
Section: Microthermometry Of Methane Inclusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abundant physical experiments (Bear, 1972;Prada and Civan, 1999;Dou et al, 2014;Wang et al, 2016;Hu et al, 2018;Tian et al, 2018;Wang and Cheng, 2020;Chi and Wang, 2021;Zhao et al, 2021;Yin et al, 2022) and theoretical analysis (Cai, 2014;Wang et al, 2018;Zhang et al, 2018;Zhang et al, 2019a;Ye et al, 2019) have demonstrated when the formation permeability is low, the seepage flow in the formation will belong to the low-velocity non-Darcian flow with a threshold pressure gradient (TPG). The TPG can introduce additional formation energy consumption, which hinders the fluid flow ability through the formation.…”
Section: Introductionmentioning
confidence: 99%